Gangnam Style versus Eye of the Tiger: people, police and procedural justice in Indonesia. (18th May 2016) - Davies, Sharyn Graham; Meliala, Adrianus; Buttle, John
Abstract : Indonesia's police force is the fifth largest in the world, and it is one of the most brutal, corrupt and ineffective. Since the forced resignation of authoritarian President Suharto in 1998, millions of dollars have been funnelled into police reform, with much of this funding coming from overseas donors such as the USA and Australia. Despite good intentions and some limited but notable success, police reform has failed to deliver tangible improvements in policing across the archipelago. There are many reasons for the failure of reform efforts, but a contributing factor is the lack of robust academic research on what kind of reform will work best for Indonesia. Without research-led reform, reform models have relied on the adaptation, or even wholesale adoption, of overseas models. As such, reforms have focused on delivering instrumental change primarily through improving the capacity of police to deter, investigate and solve crime. That reforms have been instrumentally focused presupposes that police legitimacy, fundamental to a well-functioning police service, rests on a public desire for outcome-based policing in preference to procedurally just policing. Until now there has been no research to contribute an empirical base to this assumption in Indonesia. To begin filling this void, long-term ethnographic fieldwork was conducted by the first author to examine public perceptions of police. In evaluating citizen narratives, our research shows that the procedural justice model of policing dominates assessments of police over and above instrumental concerns. Part of the reason for the importance of procedural justice vis-à-vis instrumentality relates to kinships of shame that configure respect as a foundation of social legitimacy. A large-scale quantitative study is needed to extend our findings beyond its ethnographic base, and if our findings are supported, reform efforts will do well to acknowledge that procedural justice policing will improve police legitimacy in Indonesia more substantively than instrumental policing.